2008
DOI: 10.1128/mcb.02375-06
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Roles of β-Catenin and Plakoglobin in LEF/T-Cell Factor-Dependent Transcription Using β-Catenin/Plakoglobin-Null F9 Cells

Abstract: ␤-Catenin functions as a transcriptional regulator in Wnt signaling. Its function is regulated by a specific destruction system. Plakoglobin is a close homologue of ␤-catenin in mammalian cells and is regulated in a similar fashion. When ␤-catenin or plakoglobin is exogenously expressed in cells, endogenous ␤-catenin is stabilized, which complicates estimation of the transcriptional activities of exogenously expressed proteins. To facilitate the design of experiments aimed at investigating the transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…Similar to ␤-catenin, plakoglobin can activate the Wnt signaling pathway, transduce signals to the nucleus, and activate lymphoid enhancer binding factor/T cell factor-dependent transcription (Simcha et al, 1998;Miravet et al, 2002;Maeda et al, 2004;Shimizu et al, 2008). It is noteworthy that plakoglobin, as well as E-cadherin, increased after Wnt-1 expression in PC-12 cells, and this strengthened cell-cell contacts (Bradley et al, 1993).…”
Section: Anchoring Junctions and Male Contraceptionmentioning
confidence: 97%
“…Similar to ␤-catenin, plakoglobin can activate the Wnt signaling pathway, transduce signals to the nucleus, and activate lymphoid enhancer binding factor/T cell factor-dependent transcription (Simcha et al, 1998;Miravet et al, 2002;Maeda et al, 2004;Shimizu et al, 2008). It is noteworthy that plakoglobin, as well as E-cadherin, increased after Wnt-1 expression in PC-12 cells, and this strengthened cell-cell contacts (Bradley et al, 1993).…”
Section: Anchoring Junctions and Male Contraceptionmentioning
confidence: 97%
“…pCAG-dE(HA) was constructed from pCAG-EM2, a mouse E-cad expression vector (Shimizu et al, 2008), by replacing the HincII-XhoI fragment with a PCR product including HA-tag sequence and several restriction enzyme sites. pAcLCL-AFP was constructed by replacing the lacZ-cassette of pAcCATZ (Araki et al, 1995) with GFP by blunt ligation.…”
Section: Plasmidsmentioning
confidence: 99%
“…PG is also found in the cytoplasm and nucleus (Green and Simpson, 2007;Schmidt and Koch, 2007), where it is able to act independently of its function in intercellular adhesion. Its adhesionindependent functions are still not well defined, but the data suggest that PG can regulate gene expression and protein stability (Aktary et al, 2010;Hakimelahi et al, 2000;Shimizu et al, 2008) in both a -catenin-dependent and -independent manner (Raurell et al, 2006;Teuliere et al, 2004;Yin and Green, 2004;Zhurinsky et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…PG is also found in the cytoplasm and nucleus (Green and Simpson, 2007;Schmidt and Koch, 2007), where it is able to act independently of its function in intercellular adhesion. Its adhesionindependent functions are still not well defined, but the data suggest that PG can regulate gene expression and protein stability (Aktary et al, 2010;Hakimelahi et al, 2000;Shimizu et al, 2008) in both a -catenin-dependent and -independent manner (Raurell et al, 2006;Teuliere et al, 2004;Yin and Green, 2004;Zhurinsky et al, 2000).Recently we demonstrated that PG not only inhibits motility of keratinocytes in contact, but also inhibits Src-dependent single cell motility (Yin et al, 2005b). The observed changes in motility and altered cell morphology of PG -/-keratinocytes suggested to us that PG could be regulating cell-substrate interactions by modulating components of the extracellular matrix (ECM), its integrin receptors and/or the molecules involved in ECM-triggered motility cues.…”
mentioning
confidence: 99%